Zika Virus-Induced Neuronal Apoptosis via Increased Mitochondrial Fragmentation - Yang, Shu; Gorshkov, Kirill; Lee, Emily M.; Xu, Miao; Cheng, Yu-Shan; Sun, Nuo; Soheilian, Ferri; de Val, Natalia; Ming, Guoli; Song, Hongjun; Tang, Hengli; Zheng, Wei (Frontiers in Microbiology, 2020)
The 2015 to 2016 outbreak of Zika virus (ZIKV) infections in the Americas coincided with a dramatic increase in neurodevelopmental abnormalities, including fetal microcephaly, in infected pregnant women and their newborns. In this study, we observed mitochondrial fragmentation and disrupted mitochondria membrane potential after 24 hours of ZIKV infection in human neural stem cells and the SNB-19 glioblastoma cell line. The severity of these changes correlated with the amount of ZIKV proteins expressed in infected cells. ZIKV infection also decreased the levels of mitofusin 2, which modulates mitochondria fusion. Mitochondrial division inhibitor 1 (Mdivi-1), a small molecule inhibiting mitochondria fission, ameliorated mitochondria changes and reduced cell death in ZIKV-infected cells. Collectively, this study suggests the abnormal mitochondrial fragmentation contributes to ZIKV-induced neuronal cell death; rebalancing mitochondrial dynamics of fission-fusion could be a therapeutic strategy for drug development to treat ZIKV-mediated neuronal apoptosis.